2016
DOI: 10.1108/edi-08-2014-0062
|View full text |Cite
|
Sign up to set email alerts
|

Understanding approaches to managing diversity in the workplace

Abstract: Purpose-The purpose of this paper is to enhance understanding of why and how companies implement diversity management in practice, and of factors that may explain their approach. Design/methodology/approach-This study takes inspiration from existing typologies depicting organisation-wide perspectives on diversity management, and articulates them in more detail by applying practice-driven indicators and highlighting possible contingent factors at play. The resulting framework is used to investigate diversity ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…However, studies have shown that there are some positive effects of the crisis for diversity. Some researchers found that the appearance of having diversity as a priority is good for public relations in that it signals corporate social responsibility (French and Ali, 2016;Ravazzani, 2016), which is popular with the public and investors (Sun et al, 2015). An example of positive outcomes is the tendency of some boards to increase diversity among board members during financially difficult times; 'one is a token, two is a presence, three is a voice' (Gyapong et al, 2016: 373).…”
Section: Positive Aspects For Diversity In the Context Of The Economimentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies have shown that there are some positive effects of the crisis for diversity. Some researchers found that the appearance of having diversity as a priority is good for public relations in that it signals corporate social responsibility (French and Ali, 2016;Ravazzani, 2016), which is popular with the public and investors (Sun et al, 2015). An example of positive outcomes is the tendency of some boards to increase diversity among board members during financially difficult times; 'one is a token, two is a presence, three is a voice' (Gyapong et al, 2016: 373).…”
Section: Positive Aspects For Diversity In the Context Of The Economimentioning
confidence: 99%
“…Another example is the increased number of opportunities for women at the top of the organizational ladder in hard times, although these opportunities may prove to be perilous (Sun et al, 2015). Some researchers found that the appearance of having diversity as a priority is good for public relations in that it signals corporate social responsibility (French and Ali, 2016;Ravazzani, 2016), which is popular with the public and investors (Sun et al, 2015). Although the promising harbingers of change are clear, there is more work to be done: Holgate et al (2012) remarked that newer areas of striving for equality and inclusion, such as disability, sexual orientation, religion, and age, remain relatively underdeveloped, which is consistent with the proportion of diversity indicators in the reviewed research.…”
Section: Positive Aspects For Diversity In the Context Of The Economimentioning
confidence: 99%
“…However, in recent years, researchers have shown growing interest in studying the social dimension of corporate social responsibility (CSR) as a corporate duty and a part of business integral to human resources (HR) [9,10]. Ravazzani investigated the implementation of diversity management by looking at managerial interventions and contextual factors that influence business activities [10]. This research shows that companies in Italy work with social factors as an isomorphic expectation to gain legitimacy in society for their business.…”
Section: Introductionmentioning
confidence: 99%
“…After then the concept developed; to be connected with planned actions of fair human resources strategies that aim to reach the optimal synergy between diverse human resources (Henry & Evans 2007;Ravazzani, 2016) . (Shen et al, 2009 ; believed that to maximize the benefits of having diverse human resources the attempts must go beyond the traditional approaches of celebrating differences; compliance to the state law, fair human resources strategies aren't any more enough.…”
Section: Diversity Management Objectivesmentioning
confidence: 99%